Konsep dan Perlindungan Hukum Penyalahgunaan Anak Dalam Penyelenggaraan Pemilu - Nellyati Makkarumba; Abrar Lafi Naim (Badan Pengawas Pemilihan Umum, 2022)
The unjustifiable abuse of children in the holding of general elections is a form of violation at the campaign stage. Involving children or citizens who do not have the right to vote in political campaign activities is not the right decisions, because children have same right to be free from abuse of any political activities. This writing aims to analyze the forms and offer the concept of diversion as protection against child abuse in the General Election. The research method of this paper is using the type of research normative-empirical. The paper also used statutory approach and conceptual approach. The procedure for collecting materials uses a literature study with combination of descriptive qualitative. The results obtained that the concept of diversion in handling election crimes in which the perpetrators and victims are children can be applied in handling general election violations by the Center of Integrated Law Enforcement Bawaslu, this indicates the importance of further regulation by reformulation and harmonization in the laws and regulations concerning General Elections and it takes effort development of a pattern of repressive and preventive prevention and enforcement strategies in order to provide child-friendly legal protection.